The combination effect of tetracycline with bitter gourd (Momordica charantia) fruit extract and gallic acid on antimicrobial against pathogens - Patathananone, Supawadee; Lareenu, Noliza; Siripat, Prattanah; Klaynongsruang, Sompong; Daduang, Sakda (Journal of Applied Research on Science and Technology (JARST), 2018)
Antibiotic drugs resistant of the pathogenic microorganism problem has increased rate in the current. The single antibiotic substances often potential decrease for therapy. Thus, the multiple combinations of antimicrobial agents are a new strategy for improving this problem. Natural products are the sources of antimicrobial substances which are developed for antibiotic combination. In this research, the antimicrobial effect of phytochemical compounds, gallic acid and caffeic acid, bitter gourd fruit extracts and tetracycline which is representative of antibiotic drug on the growth of Pseudomonas aeruginosa ATCC 27853 and Staphylococcus aureus ATCC 25923 were determined. Then, the combined effects of bitter gourd fruit extracts and gallic acid with tetracycline were determined using checkerboard assay and analyzed by FIC Index. The result showed that all treatment samples inhibited growth of both pathogenic bacterial cells in vitro. The MIC values of bitter gourd fruit extracts, gallic acid and tetracycline on Ps. aeruginosa were 12000, 2000 and 16 µg/ml, respectively. Additionally, MIC dose on S. aureus showed 16000, 6000 and 1 µg/ml, respectively. Antagonistic effect was observed with the combination of bitter gourd fruit extracts and tetracycline as evidenced by high values of the FIC index on Ps. aeruginosa and S. aureus around 5.33 and 6.50, respectively. However, the combination effect of gallic acid and tetracycline showed an additive effect with the values of the FIC index of Ps. aeruginosa and S. aureus 3.00 and 0.83, respectively